2011
DOI: 10.3390/molecules16065268
|View full text |Cite
|
Sign up to set email alerts
|

Acute Oral Toxicity of Methanolic Seed Extract of Cassia fistula in Mice

Abstract: Background and objective: Cassia fistula is widely used in traditional medicine to treat various types of ailments. The evaluation of toxic properties of C. fistula is crucial when considering public health protection because exposure to plant extracts can result in undesirable effects on consumers. Hence, in this study the acute oral toxicity of C. fistula seeds extract was investigated in mice. Results: Oral administration of crude extract at the highest dose of 5000 mg/kg resulted in no mortalities or evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(166 citation statements)
references
References 24 publications
(19 reference statements)
8
143
0
6
Order By: Relevance
“…Organ weight is an important index to detect whether the organ was exposed to the injury or not (Jothy , 2011). Findings from this study revealed that the observed signif icant decreased in the weight of the liver of rats treated with hexane extract was not corroborated by both the histological examination and other biochemical parameters of liver function and therefore indicating that the extract is virtually nontoxic.…”
Section: Discussionmentioning
confidence: 67%
“…Organ weight is an important index to detect whether the organ was exposed to the injury or not (Jothy , 2011). Findings from this study revealed that the observed signif icant decreased in the weight of the liver of rats treated with hexane extract was not corroborated by both the histological examination and other biochemical parameters of liver function and therefore indicating that the extract is virtually nontoxic.…”
Section: Discussionmentioning
confidence: 67%
“…Oral chronic toxicity testing in rats could be used to evaluate natural remedies for different pharmacological activities, taking into account the basic premise that pharmacology is simply toxicology at a lower dose. 20 Histological examination of the liver, pancreas and kidney did not reveal any morphological changes after administration of STLE. The result from this study is in accordance with the other plant extracts such as leaf extract of Carica papaya Linn, 15 rhizomes extract from Ocimum tenuiflorum (Linn.)…”
Section: Discussionmentioning
confidence: 99%
“…The appearance and behavioral parameters of animals after drug administration is indicator of the toxicity of the test drug [6] [7]. The behavioral patterns of animals were observed first 6 h and followed by 14 h after the administration.…”
Section: General Appearance and Behavioral Observationsmentioning
confidence: 99%